Analisis Ketersedian dan Keterjangkauan Sarana Prasarana di Kelurahan Mawang Kecamatan Somba Opu Kabupaten Gowa - Amat Solleh (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Mawang Village occupies a strategic position as a buffer zone integrating the administrative center of Gowa Regency with other growth centers, featuring the ecological asset of Lake Mawang, which holds significant potential for ecotourism development. However, a discrepancy exists between spatial planning policies and the actual development of facilities and infrastructure on the ground. This study aims to identify the availability, accessibility, and physical feasibility of regional facilities and infrastructure as a fundamental database for area development. The method employed is descriptive-quantitative with a comparative analysis approach referring to the SNI 03-1733-2004 standards and spatial analysis. The findings indicate that religious and commercial/service facilities exhibit very high service levels with surplus conditions, while basic health facilities and early childhood education remain below minimum service standards. Spatially, the distribution of facilities tends to be concentrated along the main corridor, creating accessibility disparities for residents in inner residential areas. The collector road infrastructure is functionally adequate but lacks pedestrian facilities, while local roads suffer from pavement quality degradation. Furthermore, Lake Mawang, as a primary tourist attraction, still lacks basic supporting facilities. The implications of this research emphasize the need for equitable distribution of health facilities, revitalization of road quality, and the formulation of a comprehensive spatial detail plan for the lake area to achieve sustainable regional development based on local potential.